2016
DOI: 10.1042/bj20150274
|View full text |Cite
|
Sign up to set email alerts
|

Autism-associated R451C mutation in neuroligin3 leads to activation of the unfolded protein response in a PC12 Tet-On inducible system

Abstract: The expression of the autism-related mutant R451C neuroligin3 activates the three branches of the unfolded protein response in neuronal-like PC12 cells and leads to up-regulation of the response target genes BiP and CHOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 47 publications
(59 reference statements)
4
37
0
Order By: Relevance
“…The current knowledge regarding the role of ER stress in the pathophysiology of ASD is mainly based on data from autism-associated mutations in synaptic genes such as NLGN3, CNTNAP2, and CADM1 [19,20,21,22,23,24]. Our data provide the first evidence of altered ER stress genes in the brain of ASD subjects.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The current knowledge regarding the role of ER stress in the pathophysiology of ASD is mainly based on data from autism-associated mutations in synaptic genes such as NLGN3, CNTNAP2, and CADM1 [19,20,21,22,23,24]. Our data provide the first evidence of altered ER stress genes in the brain of ASD subjects.…”
Section: Resultsmentioning
confidence: 59%
“…In particular, genetic variations in several synaptic genes implicated in ASD have been shown to induce ER stress genes. Overexpression of neuroligin (NLGN) 3 mutant has been shown to activate the UPR downstream of the stress sensors ATF6, IRE1, and PERK [21]. Mutated GPR85 resulted in ER stress and impaired dendrite formation of hippocampal neurons [22].…”
Section: Introductionmentioning
confidence: 99%
“…The emerging evidence shows that ER stress is associated with the pathogenesis of autism(Fujita-Jimbo et al , 2015; Fujita et al , 2010; Momoi et al , 2010; Ulbrich et al , 2015). Genetic testing in individuals with autism has identified mutations in several genes encoding synaptic cell adhesion molecules, such as neuroligin-3 and -4 (NLGN-3 and -4)(Jamain et al , 2003) and cell adhesion molecule-1 (CADM-1)(Zhiling et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic testing in individuals with autism has identified mutations in several genes encoding synaptic cell adhesion molecules, such as neuroligin-3 and -4 (NLGN-3 and -4)(Jamain et al , 2003) and cell adhesion molecule-1 (CADM-1)(Zhiling et al , 2008). It has been shown that mutated NLGN-3 and CADM-1 induce local misfolding and cause partial retention of proteins in the ER that lead to ER stress in PC12 and C2C5 cell models(Fujita, et al , 2010; Ulbrich, et al , 2015). Overexpression of mutated NLGN-3 leads to the activation of three ER stress signals, as well as their downstream genes, such as BiP and CHOP in PC12 cells(Ulbrich, et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation